To solve the equation \( ? \times \left[ 1 - \frac{1}{6}(4 + 2^3) \right] = 7 \), we'll first simplify the expression inside the brackets.
-
Calculate \( 2^3 \): \[ 2^3 = 8 \]
-
Substitute \( 8 \) back into the expression: \[ 4 + 2^3 = 4 + 8 = 12 \]
-
Now, substitute \( 12 \) into the equation: \[ 1 - \frac{1}{6}(12) \]
-
Calculate \( \frac{1}{6}(12) \): \[ \frac{12}{6} = 2 \]
-
Now substitute \( 2 \) back into the equation: \[ 1 - 2 = -1 \]
Now we can rewrite the equation as: \[ ? \times (-1) = 7 \]
To find \( ? \): \[ ? = \frac{7}{-1} = -7 \]
So, the value of \( ? \) is \( \boxed{-7} \).